Brake power, brake spesific fuel consumption, dan brake thermal efficiency mesin diesel injeksi langsung berbahan bakar solarjatropa-butanol - Syarifudin Syarifudin; Syaiful Syaiful; Firman Lukman Sanjaya (TURBO [Tulisan Riset Berbasis Online], 2020)
Jatropha is proven to reduce dependence on diesel fuel. Jatropha oil is widely used as  a mixture of diesel fuel. However, low heating value and high viscosity result in lower engine performance and higher carbon black emissions than pure diesel fuel. Alcohol groups such as butanol have low viscosity properties and oxygen and cetane numbers close to diesel fuel. The use of butanol as an additive to diesel-jatropha mixed fuels is expected to improve engine performance. This study aims to observe brake power, brake specific fuel consumption, and brake thermal efficiency of diesel engines using diesel-jatropha-butanol mixed fuel. Jatropha used 10%, 20% and 30%. While the butanol used is 5%, 10%, and 15% based on volume. The research increased in a brake power value of 2.22%. The decrease in brake specific fuel consumption was 4.81% and the increase in brake thermal efficiency was 10.85%.Keywords : jatropha, viscosity, performance, soot, butanol.